ANALISIS PENGENDALIAN KUALITAS PRODUK PADA ROTI GEPENG ZB SAMARINDA - Ariza Miftakhul Rahman; Ali Mushofa; Mardiono Mardiono (University of Widya Gama Mahakam Samarinda, 2019)
Analysis of Product Quality Control on ZB Gepeng Samarinda Bread, The purpose of this study is to identify what factors cause damage to bread products and to determine the extent to which the application of statistical aids can be used to control the quality of bread products. This research method is descriptive quantitative using statistical aids found in statistical quality control to determine whether the production process is controlled or not employing a control chart p and cause-effect diagram. From the results of the analysis, it is known that the average damage in each production is 2% in the first quarter and 2.3% in the second quarter, with the total cost overall is 2.2%. The 2.2% value is quite good because the average damage in production is not significant compared to the tolerance limit of 4%. From the causal diagram analysis, it can be seen that the damage factor in the production of flatbread is derived from human factors or in this case employees, production tools, work methods, and materials or raw materials